2017
DOI: 10.1021/acs.cgd.7b00324
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Ionic Bond and Solubility Mechanism of NanPQQ (n = 0–4) Crystals

Abstract: A comparative study of van der Waals and ionic crystals can provide vital information for the medical and food industries. In this work, we investigated the coenzyme pyrroloquinoline quinone (PQQ), which contains three carboxyl groups coupled to imidazole, pyridine, and quinone. Whole-crystal analysis (crystal-ome) was attempted for Na n PQQ (n = 0–4) crystals. All deprotonation sites were found to be dependent on pK a except for the Na sites, which cannot be explained by pK a. The Na1PQQ crystal exhibited an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…While no Ca-PQQ structure has been published to date, in addition, few other crystal structures exist for PQQ with other metals. Outside of the Ca-MDH network (Blake et al, 1994;Williams et al, 2005), several structures were published with sodium ISSN 2053-2296 (Ishida et al, 1989;Ikemoto et al, 2012;Ikemoto et al, 2017), with PQQ structural analogs and iron (Tommasi et al, 1995), with copper and terpyridine (terpy) as co-ligand (Nakamura et al, 1994), with copper and triphenylphosphine (Wanner et al, 1999), with ruthenium and terpy (Mitome et al, 2015), and with ruthenium, silver and terpy (Mitome et al, 2013). In 2014, Pol et al reported a new kind of MDH, found in the extremophile Methylacidiphilum fumariolicum SolV (SolV), which is native to volcanic mudpots close to the Solfatara crater in Italy (Pol et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While no Ca-PQQ structure has been published to date, in addition, few other crystal structures exist for PQQ with other metals. Outside of the Ca-MDH network (Blake et al, 1994;Williams et al, 2005), several structures were published with sodium ISSN 2053-2296 (Ishida et al, 1989;Ikemoto et al, 2012;Ikemoto et al, 2017), with PQQ structural analogs and iron (Tommasi et al, 1995), with copper and terpyridine (terpy) as co-ligand (Nakamura et al, 1994), with copper and triphenylphosphine (Wanner et al, 1999), with ruthenium and terpy (Mitome et al, 2015), and with ruthenium, silver and terpy (Mitome et al, 2013). In 2014, Pol et al reported a new kind of MDH, found in the extremophile Methylacidiphilum fumariolicum SolV (SolV), which is native to volcanic mudpots close to the Solfatara crater in Italy (Pol et al, 2014).…”
Section: Introductionmentioning
confidence: 99%